Analysis of Water Behavior in Oil Palm Plantations on Spodosol and Ultisol Using Soil Moisture Content Monitoring System (SMCMS) - Sukarman, Sukarman; Sutiarso, Lilik; Suwardi, Suwardi; Wirianata, Herry; Prima Nugroho, Andri; Primananda, Septa; Syarovy, Muhdan; Pradiko, Iput; Hijri Darlan, Nuzul (Jurnal Penelitian Kelapa Sawit, 2024)
The availability of water is a crucial aspect for optimal growth and productivity of oil palm. This research analyzes soil water behavior by monitoring soil moisture and temperature dynamics using the Soil Moisture Content Monitoring System (SMCMS). SMCMS consists of sensors installed in the field and an internet-based monitoring system. SMCMS was installed in oil palm plantations on Ultisol (A), Spodosol with hardpan breaking and mounding treatment (B), and Spodosol without treatment (C). Soil moisture and temperature sensors were installed at three different depths. The results show that SMCMS can operate automatically and in real-time in measuring water behavior. Based on monitoring and measurement results, it can be seen that the highest soil moisture is at location A, with an average of 46.91%, followed by location B at 38.40%, and C at 29.49%. Spodosol with treatment (B) had the lowest soil temperature with an average of 27.36°C, followed by Ultisol (A) at 27.58°C and control Spodosol (C) at 28.40°C. Furthermore, soil moisture is weakly correlated with soil temperature. Soil temperature has a weak correlation with air temperature. Meanwhile, these two soil water behaviors correlate very weakly with environmental variables, especially rainfall.